The Influence of Job Performance on Employee Career Development at Truntum Hotel Padang - Saniyyah Fitri; Dwi Pratiwi Wulandari (Pt. Threeple Herphi Educate, 2025)
This study aims to analyze the influence of job performance on employee career development in the hospitality sector, with a specific focus on Truntum Hotel Padang. A quantitative research design with a causal associative approach was employed, involving a total sample of 76 permanent employees. Data were collected through a structured questionnaire and analyzed using simple linear regression with SPSS version 25. The findings reveal that job performance has a positive and significant effect on career development, with a regression coefficient (β = 0.303, p < 0.05) and an R² value of 0.064. This indicates that 6.4% of the variance in career development can be explained by job performance, while the remaining proportion is influenced by other factors. Theoretically, this study contributes to career development literature by providing empirical evidence from the Indonesian hospitality industry, which remains underexplored. Practically, the findings suggest that hotel managers should design fair appraisal systems, transparent promotion pathways, and inclusive human resource policies to enhance employee motivation and retention. The study also highlights the importance of integrating performance management with organizational support practices.